Targeted Anti‐Tumor Immunotherapy Using Tumor Infiltrating Cells. Issue 22 (18th October 2021) - Xie, Yifan; Xie, Feng; Zhang, Lei; Zhou, Xiaoxue; Huang, Jun; Wang, Fangwei; Jin, Jin; Zhang, Long; Zeng, Linghui; Zhou, Fangfang
Abstract: In the tumor microenvironment, T cells, B cells, and many other cells play important and distinct roles in anti‐tumor immunotherapy. Although the immune checkpoint blockade and adoptive cell transfer can elicit durable clinical responses, only a few patients benefit from these therapies. Increased understanding of tumor‐infiltrating immune cells can provide novel therapies and drugs that induce a highly specific anti‐tumor immune response to certain groups of patients. Herein, the recent research progress on tumor‐infiltrating B cells and T cells, including CD8 + T cells, CD4 + T cells, and exhausted T cells and their role in anti‐tumor immunity, is summarized. Moreover, several anti‐tumor therapy approaches are discussed based on different immune cells and their prospects for future applications in cancer treatment. Abstract : The progress of anti‐tumor immunity is reviewed. Recent findings of CD4 + T cell, CD8 + T cell, T cell exhaustion and B cell are provided. Several anti‐tumor immunotherapies based on different immune cells in these years and prospects of anti‐tumor immunotherapies are also discussed. The clinical trials of some immunotherapies are also reviewed.